2022
DOI: 10.2174/1871530321666210908124848
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Cholesterol Assimilation by Bifidobacterium animalis subsp. lactis (BPL1) Probiotic Bacteria Under Intestinal Conditions

Abstract: Background: Hypercholesterolemia is one of the principal causes of the development of cardiovascular diseases. Recently, probiotics consumption has been also proposed as a non-pharmacological intervention to control cholesterol concentrations. Objective: To evaluate in vitro assimilation of cholesterol by Bifidobacterium animalis subsp. lactis (BPL1) under simulated intestinal environment in anaerobic conditions and to review and discuss potential physiological mechanisms in this context. Methods: Bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…The mechanism for lowering cholesterol by Bifidobacterium spp. was not very clear until now [24]. The research also found that, after adding…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The mechanism for lowering cholesterol by Bifidobacterium spp. was not very clear until now [24]. The research also found that, after adding…”
Section: Discussionmentioning
confidence: 92%
“…The mechanism for lowering cholesterol by Bifidobacterium spp. was not very clear until now [24]. The research also found that, after adding BAs, fat digestibility was improved greatly (p < 0.05), which could reduce strain on the liver for cats.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Bacterial cells remove cholesterol from the medium by adsorption or absorption by incorporating cholesterol into the cell membrane (33). According to the recent literature data, the administration of functional food containing probiotic bacteria was effective in cholesterol assimilation under simulated GIT conditions (34). Nutrient-rich food matrices such as FSMPs might be associated with a higher capacity Please note that this is an unedited version of the manuscript that has been accepted for publication.…”
Section: Resultsmentioning
confidence: 99%
“…3) transformation of cholesterol into coprostanol and its removal from the body together with feces; 4) inhibition of cholesterol synthesis in the liver (Hassan et al, 2019;Bhat et al, 2019;Daliri et al, 2022;Alaqil et al, 2020;O'Morain & Ramji, 2020;Jia et al, 2023;Asan-Ozusaglam & Gunyakti, 2019;Park et al, 2018;Damodharan et al, 2016;Bendali et al, 2017;Singhal et al, 2019;Zhang et al, 2017;Saikia et al, 2018;Bidura et al, 2019;Majeed et al, 2019;Huang et al, 2021;Haldar & Gandhi, 2019;Tom et al, 2021;Palaniyandi et al, 2020;Yusuf et al, 2020;Fernandez-Calderon et al, 2022).…”
mentioning
confidence: 99%